Processo de reparo ósseo diante de três tipos de superfície de titânio: análise histomorfométrica e por microscopia eletrônica de varredura associada ao EDS: estudo experimental - Francisconi, Giovanna Barbosa [UNESP] (2014)
Purpose: Given the positive influence of the surface treatment of implants in the healing and/or peri-implant bone regeneration process, we proposed on this study histologically characterize the newly formed bone tissue under different titanium surfaces. Material and Methods: Surgical procedures were performed on 75 rats (Rattus norvegicus Albinus, Wistar) were divided into 3 groups of 25 animals, where we had access to the upper third of the right tibia of each rat for the subsequent installation of the implants. The first group received the implant polished surface (POLISHED GROUP - GP), the second received an implant with machined surface (MACHINED GROUP - GU) and the third group received the implant surface treated with acid (TREATED GROUP - GT). In total there were 3 groups, 25 implants per group and 1 implant per animal. In periods of 3, 7, 15, 21 e 40 postoperative day, the animals were euthanized and tissue samples obtained were submitted to the histomorphometric analyses by scanning electron microscopy (SEM) and were performed by Energy Dispersive X Ray Spectroscopy (EDS). Results: The results of SEM analysis of the surfaces showed topographical differences among them being the most smooth and regular surface of the GP, then the surface of the GU and, finally, with greater surface roughness, the GT. Comparing the BIC values of the three groups for the same period (measuring both cortical as trabecular region of the tibia), a statistically significant 17 difference (p <0.05) was found only in the initial period of osseointegration (7 days) between the GP and GT values, where p = 0.0189 and the BIC percentage was 70% and 94%, respectively. Conclusion: The process of osseointegration of implants happened with same quality standard in both polished surfaces (GP), as on machined (GU) and treated with acid subtraction (GT). In contact with the surface...